Shear Wave Splitting Across Antarctica: Implications for Upper Mantle Seismic Anisotropy. Issue 4 (29th March 2022) - Lucas, Erica M.; Nyblade, Andrew A.; Accardo, Natalie J.; Lloyd, Andrew J.; Wiens, Douglas A.; Aster, Richard C.; Wilson, Terry J.; Dalziel, Ian W.; Stuart, Graham W.; O'Donnell, John Paul; Winberry, J. Paul; Huerta, Audrey D.
Abstract: We examine upper mantle anisotropy across the Antarctic continent using 102 new shear wave splitting measurements obtained from teleseismic SKS, SKKS, and PKS phases combined with 107 previously published results. For the new measurements, an eigenvalue technique is used to estimate the fast polarization direction and delay time for each phase arrival, and high‐quality measurements are stacked to determine the best‐fit splitting parameters at each seismic station. The ensemble of splitting measurements shows largely NE‐SW‐oriented fast polarization directions across Antarctica, with a broadly clockwise rotation in polarization directions evident moving from west to east across the continent. Although the first‐order pattern of NE‐SW‐oriented polarization directions is suggestive of a single plate‐wide source of anisotropy, we argue the observed pattern of anisotropy more likely arises from regionally variable contributions of both lithospheric and sub‐lithospheric mantle sources. Anisotropy observed in the interior of East Antarctica, a region underlain by thick lithosphere, can be attributed to relict fabrics associated with Precambrian tectonism. In contrast, anisotropy observed in coastal East Antarctica, the Transantarctic Mountains (TAM), and across much of West Antarctica likely reflects both lithospheric and sub‐lithospheric mantle fabrics. While sub‐lithospheric mantle fabrics are best associated with either plate motion‐induced asthenospheric flow or small‐scale convection, lithospheric mantle fabrics in coastal East Antarctica, the TAM, and West Antarctica generally reflect Jurassic—Cenozoic tectonic activity. Plain Language Summary: Seismic anisotropy, the directionally dependent variation in seismic wave speed, is widely considered to be one of the best indicators of past and present deformation and flow in the upper mantle. When the mantle deforms or flows, olivine crystals often become oriented in a systematic direction. Measurements of seismic anisotropy delineate the direction in which olivine crystals in the upper mantle are aligned and provide useful information about the tectonic history and current mantle flow in a region. In this study, we use seismic waves from distant earthquakes recorded at seismometers located in Antarctica to measure upper mantle anisotropy. Our measurements generally indicate that seismic waves travel the fastest in a northeasterly southwesterly direction in the upper mantle across much of Antarctica. The relatively uniform seismic anisotropy that we measure across Antarctica is suggestive of a single source of origin; however, we conclude that the observed anisotropy must arise from several sources, including past tectonic activity and active mantle flow beneath Antarctica. Key Points: One hundred two new and revised shear wave splitting measurements using teleseismic SKS, SKKS, and PKS phases are reported Predominantly Grid northeast‐southwest oriented fast polarization directions are found across Antarctica Anisotropy can be attributed to relict lithospheric fabrics, plate motion‐induced asthenospheric flow, and small‐scale convection